Accounting and psychiatric power in Italy: The royal insane hospital of Turin in the 19th century. (June 2019) - Funnell, Warwick; Antonelli, Valerio; D'Alessio, Raffaele
Abstract: This paper identifies the importance of accounting practices in the successful operation of the Royal Insane Hospital of Turin, prior to the Italian unification, to show the importance of the lunatic asylum to our understanding of the way in which power is sustained by the State and the dependence of this process on the information and discourses created by accounting practices. The study is informed by insights from Michel Foucault's work on lunatic asylums and psychiatric power. Accounting practices of the Royal Insane Hospital of Turin allowed the State as a major contributor to the funding of the asylum to control and monitor the cost of providing the necessary facilities and care for patients. Accounting allowed the hospital to be managed more efficiently which, most importantly, allowed the hospital to provide the support and facilities which were essential for creating the environment required for new medical practices in the treatment of the mentally unwell at a time when the role of doctors was becoming increasingly important. Accounting is also shown to have played a prominent role in supporting the political and social legitimation of the institution and its claim for public and private support. Critical to this process was the social and political importance of the statistics produced by the doctors of the lunatic asylum.